"After Calais": creating and managing (in)security for refugees in Europe. Issue 4 (December 2018) - Freedman, Jane
Abstract In October 2016, the dismantlement of the main refugee camp in the Calais region began. This camp, often known as the "Jungle" had become a symbol of the refugee "crisis" at the heart of Europe, at once a growing point of contention between the British and French Governments both claiming that they were attempting to secure their borders, and a visible reminder of the insalubrious and insanitary conditions in which refugees were living in European borderlands. Following the destruction of the camp refugees was dispatched to various reception centres across France, but these have proved largely unsuitable to their needs, and in some cases have facilitated deportation. Meanwhile, refugees have continued to come to Calais and remain subject to restrictive policing and "security" policies. This article will examine the "mismanagement" of the refugee camps in and around Calais, arguing that French government policy has been largely reactive, led by competing and often contradictory demands coming from various sources at local, international or European levels. This non-intervention can be seen as creating insecurity through inaction: leaving refugees to endure insalubrious and dangerous conditions as various political authorities seem to hope that the "problem" of Calais will disappear. Further, attempts to "secure" borders have led to increasingly insecure conditions for the refugees themselves, and have made it more difficult for those who are attempting to support them. Finally, the failure of the French and British governments to propose any suitable long-term solution to the issue of refugees in Calais can be seen as a reflection of the wider failure of EU policies, and of the ways in which inaction and mismanagement can in itself constitute a form of violence against these refugees.